Hello
To solve this question, we are asked to use substitution method.
The given equation is
![\begin{gathered} 3x+y=2\ldots\text{equ(i)} \\ y-x=-6\ldots\text{equ(}ii) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/98oqvjf6isj6r5vraolakvdcu57nnyjyq1.png)
From equation (ii), let's make y the subject of formula
![\begin{gathered} y-x=-6 \\ y=x-6\ldots\text{equ(}iii) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/setcch99i3q364cb975j26rxl5xumrjf4t.png)
Put equation (iii) into equation (i)
![\begin{gathered} 3x+y=2 \\ y=x-6 \\ 3x+(x-6)=2 \\ 3x+x-6=2 \\ \text{collect like terms} \\ 4x=2+6 \\ 4x=8 \\ \text{divide both sides by the coefficient of x} \\ (4x)/(4)=(8)/(4) \\ x=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/552ymohrg509bphwwnqyaiyp18c1o1423l.png)
We have the value of one of the ordered pair and we can use it to find the other one.
Put x = 2 in either equation (i) or (ii)
Using equation (ii)
![\begin{gathered} y-x=-6 \\ x=2 \\ y-(2)=-6 \\ \text{collect like terms} \\ y=-6+2 \\ y=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r7sx0oyoy5pqu516zvrup5ifgrolot4ev7.png)
The value of x and y is (2, -4) and the ordered pair can be written as (2, -4)